Bentuk Interogatif Bahasa Manggarai Dialek Kolor pada Masyarakat Waerana Kabupaten Manggarai Timur - Vildiana Rosariana Meiharjo; Yosef Demon (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The problem of this research is the form and meaning of the interrogative language of Manggarai, Kolor dialect in the Waerana community of East Manggarai Regency. The aim is to find and describe the form and meaning of the interrogative language of the Manggarai language, the Kolor dialect in the Waerana community of East Manggarai Regency. The approach used is a qualitative approach. The data collection used the listening and proficient method with the technique of listening to be proficient, engaging, taking notes, and recording techniques. The data collected is in the form of oral data. The theory used is the syntactic theory. Data analysis using inductive analysis model. The results showed that the interrogative form of the Manggarai language in the Kolor dialect in the Waerana community of East Manggarai Regency has two forms, namely formed by using basic question words, like what is "what", sei "who", piza'berapa 'so'o' why 'and one 'where' there are several kinds of found, namely (1) what 'what' (2) sei 'who' (3) 'how many' pizza into several types, namely ('how much' pizza, 'how much' moripiza, 'how much' mukupiza weropizan 'when', sepizan 'when'), (4) one 'where', (one 'where', paleonen 'where', zoone 'where' and pu'uone 'from where' and samaone 'how'), ( 5) so'o 'why', (so'o 'why', overo'o 'why', so'otara 'why' and nukuso'o 'how'), and use a question intonation. The meaning contained in this research is the meaning of asking for objects, asking people (humans), asking for time, asking for the number / number, asking for place / origin and asking opinions or thoughts from other people.